Mechanical Regulation of Nuclear Translocation in Migratory Neurons - Nakazawa, Naotaka; Kengaku, Mineko (Frontiers in Cell and Developmental Biology, 2020)
Neuronal migration is a critical step during the formation of functional neural circuits in the brain. Newborn neurons need to move across long distances from the germinal zone to their individual sites of function; during their migration, they must often squeeze their large, stiff nuclei, against strong mechanical stresses, through narrow spaces in developing brain tissue. Recent studies have clarified how actomyosin and microtubule motors generate mechanical forces in specific subcellular compartments and synergistically drive nuclear translocation in neurons. On the other hand, the mechanical properties of the surrounding tissues also contribute to their function as an adhesive support for cytoskeletal force transmission, while they also serve as a physical barrier to nuclear translocation. In this review, we discuss recent studies on nuclear migration in developing neurons, from both cell and mechanobiological viewpoints.